Outcome of children with multiply relapsed B-cell acute lymphoblastic leukemia: a therapeutic advances in childhood leukemia & lymphoma study. Issue 11 (November 2018) - Sun, Weili; Malvar, Jemily; Sposto, Richard; Verma, Anupam; Wilkes, Jennifer; Dennis, Robyn; Heym, Kenneth; Laetsch, Theodore; Widener, Melissa; Rheingold, Susan; Oesterheld, Javier; Hijiya, Nobuko; et al.
Abstract The survival of pediatric patients with multiply relapsed and/or refractory (R/R) B-cell acute lymphoblastic leukemia has historically been very poor; however, data are limited in the current era. We conducted a retrospective study to determine the outcome of multiply R/R childhood B-ALL treated at 24 TACL institutions between 2005 and 2013. Patient information, treatment, and response were collected. Prognostic factors influencing the complete remission (CR) rate and event-free survival (EFS) were analyzed. The analytic set included 578 salvage treatment attempts among 325 patients. CR rates (mean ± SE) were 51 ± 4% for patients with bone marrow R/R B-ALL who underwent a second salvage attempt, 37 ± 6% for a third attempt, and 31 ± 6% for the fourth through eighth attempts combined. For patients achieving a CR after their second, third, and fourth through eighth attempts, the 2 year EFS was 41 ± 6%, 13 ± 7%, and 27 ± 13% respectively. Our results showed slight improvement when compared to previous studies. This is the largest and most recent study to date that evaluates the outcome of this patient population. Our data will provide detailed reference for the evaluation of new agents being developed for childhood B-ALL.